2021
DOI: 10.1108/mmms-05-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of structural parameters for the sound absorption performance of a cellular ceramic foam

Abstract: PurposeThe purpose of this paper is to provide an optimization schedule of structural parameters for the sound absorption performance of a cellular ceramic foam in the sound frequency range of 200–4,000 Hz.Design/methodology/approachThe cellular ceramic foam with porosity of about 60–75% and the pore size of about 1–7 mm was successfully prepared by using natural zeolite powder as the main raw material. For this ceramic foam, the sound absorption performance was measured, and the absorption structure was optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Porous sound-absorbing materials are one of the most widely used sound-absorbing materials, which have good sound-absorbing performance in the highfrequency band, including fibers, [99][100][101][102] foam, [103][104][105][106] and particle [107][108][109][110] sound-absorbing materials. Within porous materials, there are a lot of tiny pores that link to the outside world and each other.…”
Section: Pvdf-based Porous Sound-absorbing Materialsmentioning
confidence: 99%
“…Porous sound-absorbing materials are one of the most widely used sound-absorbing materials, which have good sound-absorbing performance in the highfrequency band, including fibers, [99][100][101][102] foam, [103][104][105][106] and particle [107][108][109][110] sound-absorbing materials. Within porous materials, there are a lot of tiny pores that link to the outside world and each other.…”
Section: Pvdf-based Porous Sound-absorbing Materialsmentioning
confidence: 99%
“…Ceramic foams are widely used in engineering fields, and their pore size can be controlled, with the porosity of generally between 20%–95%. They are usually used as functional materials for filtration, separation, air distribution, heat insulation and bioceramics (Buncianu et al ., 2020; Hu et al ., 2014; He et al ., 2022; Sun and Liu, 2021). In addition, they may also be used for sound absorption (Sun and Liu, 2021; Duan et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They are usually used as functional materials for filtration, separation, air distribution, heat insulation and bioceramics (Buncianu et al ., 2020; Hu et al ., 2014; He et al ., 2022; Sun and Liu, 2021). In addition, they may also be used for sound absorption (Sun and Liu, 2021; Duan et al ., 2012). Compared with polymer foams, ceramic foams have some advantages, such as high temperature resistance, fire resistance, corrosion resistance and high mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…J.X. Sun et al [7] prepared the cellular ceramic foam by using natural zeolite powder as the main raw material and found that sample thickness is the main factor, air gap depth is the second and both of pore size and porosity would have a relatively slight effect on the performance. The aforementioned results conclusively demonstrate that the physical and mechanical properties of porous materials are contingent upon their microstructures, including pore structure, porosity, pore size, and other factors.…”
Section: Introductionmentioning
confidence: 99%